The use of a single case design to investigate the effect of a pre-performance routine on the water polo penalty shot - Marlow, C.; Bull, S. J.; Heath, B.; Shambrook, C. J. (Journal of Science and Medicine in Sport, 1998)
Summary The purpose of this study was to assess the effectiveness of an individualized pre-performance routine (PPR) on water polo penalty shot performance. Recent research has suggested that the use of a pre-competition routine can assist the athlete in attaining an optimal physical and psychological state that facilitates performance. Pre-performance routines have been proposed to enhance performance of closed-skill sports (not interactive in nature) by influencing concentration and enhancing the recall of optimal psychological and physiological states. While penalty shots in water polo and competitive swimming are different "beasts", the use of a PPR to attain an optimal state prior to competition can be beneficial in both cases. In the study, a single subject research design was implemented; this allows us to analyze each athlete as a unique case as well as compare findings across cases. Three experienced male water polo players (ages 22, 23, and 30) were the subjects; testing coincided with the water polo season so training and competitions were occurring during the 8-week project. The athletes were tested on the accuracy of 15 penalty shots each week for 8 weeks [a validated 11 point scoring scale was used by 2 independent scorers to assess the accuracy of the shots]. At different times for each of the 3 athletes (after week 2, 3, and 4), an intervention occurred. In this intervention, the athletes were educated on PPR and helped in designing a multi-component PPR, which was rehearsed and then implemented prior to subsequent testing. Across the three athletes, different times for PPR implementation were used to help rule out the influence of extraneous variables. The PPR consisted of concentration cues, deep breaths for relaxation, imagery and a cue word. It was hypothesized that penalty shot performance would be significantly improved AFTER each athlete began implementing PPR's. Various statistical analyses were used to assess whether or not performance improved from pre-intervention to post-intervention. Findings All three subjects demonstrated meaningful and significant improvements in performance from the pre-intervention phase to the post-intervention phase (21%, 28%, and 25% improvements in performances after PPR was introduced); meaning each athlete was able to execute more accurate penalty shots. Furthermore, each player was interviewed to ascertain his perceptions as to the effectiveness of the PPR. All three subjects reported positive perceptions about the use of pre-performance routines. Implications While differences between swimming and water polo are evident, similarities also exist such as both sports being closed-skill sports. So, there is reason to suggest that the use of an individualized pre-performance routine could facilitate swimming performance, similar to the positive impact it had in water polo (but, I'll leave that up to you to decide). The PPR could be implemented in the time leading up to the race or when the athlete is behind the blocks and trying to manage all the internal and external "noise". A multitude of challenges and tasks must be dealt with at this time and it seems that the use of a PPR might be effective in addressing some of these pre-competition challenges/ tasks. Findings from this case study research suggest that the use of a PPR, comprised of a consistent pattern of thoughts and actions, can help athletes to create or maintain an optimal pre-race physical and psychological state that facilitates performance. Lastly, of great importance, is the athlete's perception of the value of using a PPR. We all know the power of belief ... if swimmers believe in the benefits of PPR and they develop and use a PPR, then we're bound to see positive results.